The police and citizens as co-producers of crime prevention in Johannesburg - Mary S. Mangai; Anjewayne Clive Pillay; Tyanai Masiya; Stellah Lubinga (Administrative Sciences, 2023)
The city of Johannesburg is the largest metropolitan municipality out of eight in South Africa. It is notorious for its high levels of crime, with a crime index of 80.72 and a safety index of 19.28. This article examines crime prevention co-production in the Johannesburg metropolitan area. The purpose of the study was to analyse how co-production of crime prevention is organised in Johannesburg and to understand the effectiveness of the practice there. Collaborations between the regular producers (police) and citizens were assessed to fully determine the potential of crime prevention co-production. This led to qualitative interviews with 20 police officers from 10 police stations in the Johannesburg metropolitan area. A citizen survey was conducted with a selected sample from the population (n = 400) residing in the neighbourhoods covered by the police stations investigated. The findings indicate that police officers have devised practices and programmes to co-produce crime prevention. These include the sharing of pamphlets and crime prevention education and awareness during school visitations, the use of Zello technology, community police forums, and information sharing at the youth desk and in WhatsApp groups. Nevertheless, these practices do not seem to be popular among the citizens. There is a contradiction in the perception of successful crime prevention co-production between citizens and the police. This is mainly due to citizens' lack of trust in the police. The study acknowledged the importance of the work carried out by the police in crime prevention co-production but also observed the citizens' lack of trust in the police as a potential threat to crime prevention co-production. Trust is crucial in managing information sharing on crime prevention. Front line professionals, such as the police, will not be able to meet future crime challenges if there is a trust deficit. Hence, it is important to restore trust in the work carried out by the police. Professionals in public administration could learn about the importance of trust in their crucial role of implementing policies, government programmes, and service delivery.
Keywords: 350; citizens; co-production; crime prevention; Johannesburg; regular producers; trust